RESEARCH INSTRUMENT FOR VOCATIONAL HIGH SCHOOL (SMK) TEACHERS’ INSTRUCTIONAL INNOVATION: VALIDITY AND RELIABILITY ANALYSITITLE - Ufiya Putri Adhiyati; Ai Solihah; Andi Hermawan (Cakrawala Pedagogik, 2026)
Learning innovation is an important aspect of improving the quality of vocational education and strengthening teachers’ human resources. However, measuring teachers’ instructional innovation still requires an instrument that is practical, easy to use, and demonstrates adequate psychometric quality. This study aims to examine an instructional innovation instrument for Vocational High School (SMK) teachers by testing its validity and reliability using a quantitative survey approach. The instrument was developed based on a review of the literature on instructional innovation and educational human resource development, and then empirically tested through item–total correlation analysis and Cronbach’s Alpha coefficient using SPSS 26. Data were collected from 30 SMK teachers using a five-point Likert-scale questionnaire. The results showed that 19 out of 20 statement items met the validity criteria with correlation coefficients ? 0.361, while one item was eliminated. The reliability test produced a Cronbach’s Alpha value of 0.898, indicating excellent internal consistency. These findings confirm that the SMK teachers’ instructional innovation instrument is suitable for use as a measurement tool in vocational education contexts.